2011
DOI: 10.1111/j.1553-2712.2011.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Cost‐related Medication Nonadherence Among Emergency Department Patients

Abstract: Objectives: There has been a rapid rise in prescription drug costs over the past decade. As a result, many Americans are unable to afford their medications, especially in the current economic recession. Medication nonadherence is known to have adverse effects on health outcomes. The purpose of this study was to gain a preliminary understanding of cost-related medication nonadherence (CRMN) disclosure among screened emergency department (ED) patients and to describe the extent to which CRMN is associated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…As would be expected, most studies excluded patients who were critically ill, intoxicated, or otherwise unable to provide informed consent and therefore may not be generalizable to the entire spectrum of ED patients. Response rates were generally above 50%, but two studies had response rates below 50% and several studies did not report response rates …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As would be expected, most studies excluded patients who were critically ill, intoxicated, or otherwise unable to provide informed consent and therefore may not be generalizable to the entire spectrum of ED patients. Response rates were generally above 50%, but two studies had response rates below 50% and several studies did not report response rates …”
Section: Resultsmentioning
confidence: 99%
“…Housing quality was studied infrequently. The few studies that examined housing quality found high percentages (18%–35.9%) of patients who were concerned about the physical quality of their housing (e.g., pests, structural problems), and Mazer et al . found that housing problems were associated with cost‐related medication nonadherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although some individuals are automatically enrolled in the LIS Part D program (including dual eligibles, persons in Medicare Savings Programs and Social Security Income recipients), an estimated 2 million individuals do not receive this benefit despite being eligible, mainly due to lack of awareness of eligibility and enrollment procedures. 49 Other seniors may qualify for SPAP, which is also means tested and offers premium and copayment assistance for Part D plan participation in a number of states. 50 Finally, as we do not have charges or costs associated with each visit in our dataset, it is unclear how our findings translate into additional costs for the ED population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Andersen's Health Care Utilization Model, we chose 12 variables as possible factors affecting gender differences in CRN [23][24][25]. These 12 variables from three domains (predisposing factors, enabling factors, and need factors) are known to be robustly linked to CRN in a number of previous studies [26][27][28][29].…”
Section: Independent Variablesmentioning
confidence: 99%